2019
DOI: 10.5114/pedm.2019.84711
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the metabolic syndrome diagnosis in obese children in clinical practice

Abstract: Introduction: In the light of recent studies, the usefulness of the metabolic syndrome diagnosis in obese pediatric patients seems to be controversial. It leads to the pressing questions, if the metabolic syndrome diagnosis is reflecting risk of the cardiovascular complications in obese children. Aim of the study: To evaluate the incidence of metabolic syndrome in obese children, asses the role of insulin resistance in the metabolic complications and investigate if the diagnosis of MS has a clinical value in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Metabolic syndrome was diagnosed in 69 children (24%). 31 However, in our study, we found only 16.25% of children had metabolic syndrome. This could be due to the difference in the criteria used to diagnose MetS.…”
Section: Discussioncontrasting
confidence: 63%
“…Metabolic syndrome was diagnosed in 69 children (24%). 31 However, in our study, we found only 16.25% of children had metabolic syndrome. This could be due to the difference in the criteria used to diagnose MetS.…”
Section: Discussioncontrasting
confidence: 63%
“…Importance of diagnostics of MS for clinical practice is pointed out by Springwald et al . [ 23 ]. According to the analysis of presented results of lipid metabolism tests in our patients, we need to take into account that the mean age of the subjects was about 14 years.…”
Section: Discussionmentioning
confidence: 99%
“…FMI is a better predictor of metabolic syndrome than BMI [ 8 ]. A timely diagnosis of metabolic syndrome allows the implementation of early intervention and reduces the risk of chronic conditions later in life [ 16 , 39 ]. Nonetheless, FMI usage requires additional specialized equipment: scales capable of measuring bioimpedance or callipers.…”
Section: Discussionmentioning
confidence: 99%